ANASE: Unreliable - owing to design-induced biases - Brooker, Peter (Institute of Acoustics, 2008)
In November 2007, the ANASE (Attitudes to Noise from Aviation Sources in England) report was published. It claimed that people are increasingly annoyed by aircraft noise, and it estimated how much they would be ‘willing to pay’ to get rid of it. But its quantitative ‘findings were rejected as unreliable by the Department for Transport [DfT]’ (BBC webpage). This paper summarises the main ANASE claims, and then examines its design, methodology and statistical analyses as set out in published documents. DfT was wise to commission the peer reviews and to publish the material (rather than be accused of a ‘cover up’). But no reliance can be put on ANASE’s claims. There are unrepairable major problems with questionnaire design and process, noise estimates, analysis techniques, and selective attempts to compare with international work.